The Fetishised Role of External Actors in Zimbabwe’s 2018 Elections: Implications for the Future Plebiscites - Moyo, Gorden (Africana Studia, 2020)
This article retraces the geoeconomic contours of the external actors in Zimbabwe’s controversial 2018 elections. It surfaces the footprints of the major global actors especially the UK, the EU, and the U.S. beyond the publicly expressed democracy promotion paradigms. It also looks closely at the activities, intentions and interests of the re-emerging powers of China and Russia in the discursive context of the 2018 elections in Zimbabwe. It is the argument of this article that the external actors were deeply involved in the first post-Mugabe elections in Zimbabwe for geoeconomic, geopolitical and geostrategic interests. A rguably, the renewed interest in these elections was occasioned by Robert Mugabe’s exit from the political scene in Zimbabwe after 37 years of uninterrupted rule. The article concludes that Zimbabwe’s 2018 elections were caught up in the broader global geo-economics and geopolitical competition between the relatively declining Global North powers led by the U.S. and the re-emerging Global South powers led by China. Overall, the article argues that global powers will most likely continue to have interest in the electoral processes in Zimbabwe and that Beijing and Kremlin are likely to hold a dominant sway in the future of that country.